Low-chloride-ion coprecipitation catalyst and preparation method of polyether amine
The modified hydrotalcite-supported ion exchange resin exchanges Cl- during the catalyst preparation process, and the carbon nanotube modified hydrotalcite improves the high temperature resistance of the resin, solving the problems of catalyst poisoning and insufficient resin performance in the prior art, and achieving improvements in catalyst activity and equipment safety.
Patent Information
- Application Number
- CN202510000895.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
The metal chloride used in the preparation of existing amination catalysts leads to catalyst poisoning and inactivation, and the ion exchange resin has poor performance at high temperatures, which limits the activity of the catalyst and the safety of the equipment.
The preparation method of low chloride ion coprecipitation catalyst is adopted. By using a modified hydrotalcite-supported ion exchange resin, the Cl- in the mother liquid during the catalyst production process is exchanged to reduce the Cl- content in the catalyst, and the high-temperature resistance of the ion exchange resin is improved through carbon nanotube modified hydrotalcite.
The Cl- content in the catalyst is significantly reduced, the activity of the catalyst and the processing capacity of raw materials are improved, and the corrosion risk of chloride ions on the equipment is reduced.
Smart Images

Figure FDA0005225065670000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysis, and in particular to a preparation method of a low chloride ion coprecipitation catalyst and a polyetheramine. Background Art
[0002] Polyetheramine is a type of polymer with a polyether structural skeleton as the main chain and an amine group as the terminal active group. Most of these compounds are made from the ring-opening polymer of epoxy compounds corresponding to their structure (also known as polyether polyols). The terminal active group hydroxyl group is chemically reacted to obtain polyetheramine with an amine group as the terminal active group. Polyetheramine is widely used in many epoxy fields such as wind turbine blades, decorative glue, epoxy flooring, epoxy coatings, etc. In addition, it is also widely used in oil additives, polyurea spraying, metal cutting fluids, textiles and other industries.
[0003] In the prior art, this amination catalyst is currently often prepared by a coprecipitation method, often using cheap sodium carbonate or hydroxide as a precipitant, and mainly containing nickel, cobalt or copper as an active component, and the active metal is often used in the form of chloride.
[0004] CN110785400A discloses a method for preparing alkanolamines and ethyleneamines, which comprises preparing a catalyst precursor comprising at least one catalytically active component selected from Sn, Cu and Ni, and then contacting the precursor with a soluble Ru compound and a soluble Co compound, wherein chlorides of active metals are used in the catalyst preparation process.
[0005] CN110709379A discloses a method for preparing alkanolamines and / or ethyleneamines in a liquid phase, wherein an amination catalyst comprising Co, Ru and Sn is prepared for the reaction of ethylene glycol and / or monoethanolamine with ammonia, and active metal chlorides are also used in the preparation process.
[0006] CN103657682B discloses a catalyst for synthesizing octylamine by reductive amination of octanol and a preparation method thereof. A catalyst with Cu, Ni, Ru, and Cr as main active substances and Zn and Sn as auxiliary active substances is prepared using γ-Al2O3 or diatomaceous earth as a carrier. Active metal chlorides, especially tin chloride, are also used in the preparation process. The introduction of Sn improves the distribution of active components of the catalyst and avoids a large amount of agglomeration of active components.
[0007] CN113474326A discloses a method for preparing alkanolamines and ethyleneamines by reacting ethylene glycol and / or monoethanolamine with ammonia in the presence of a catalyst, wherein a catalyst precursor comprising at least one catalytically active component selected from Sn, Cu and Ni is prepared, and then the precursor is contacted with a soluble Re compound, and a chloride of an active metal is used in the preparation process.
[0008] Metal chlorides are used in the preparation of existing amination catalysts, and the chloride ions introduced during the use of metal chlorides cannot be effectively removed. Since the chlorine atoms have unpaired lone pairs of electrons, they are easy to react with other ions, destroying the atomic structure in the catalyst, causing some catalysts to be poisoned or even deactivated. The literature points out that the degree of catalyst poisoning caused by chlorine is hundreds or thousands of times that of sulfur and oxygen compounds. If the catalyst poisoning is caused by chlorine, the catalyst cannot be regenerated. In addition, the residual chloride ions in the catalyst will cause serious corrosion to the production equipment.
[0009] Hydrotalcite is a type of layered double hydroxide, in which the hydrogen bonds between the layer hydroxide and the interlayer anions are relatively weak, and can exchange ions with other anions through strong electrostatic interactions. Hydrotalcite has a strong anion exchange capacity, which enables it to exchange ions with a wide variety of anions. Therefore, hydrotalcite can adsorb specific harmful ions, such as Cl - 、CO3 2- .
[0010] The ion exchange resins used in the prior art often cannot be used at higher temperatures. In most cases, the use temperature must be controlled within 100° C., which greatly limits the reactivity of the resin. Summary of the invention
[0011] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a low chloride ion coprecipitation catalyst and a polyetheramine. The catalyst prepared by the method can greatly reduce the Cl - The Cl in the mother liquor during the catalyst production process was converted to - Exchange, greatly reducing the Cl in the catalyst - The introduction of chlorine improves the activity of the catalyst, increases the raw material processing capacity, and reduces the corrosion of chloride ions to the equipment.
[0012] Another object of the present invention is to provide such amination reaction catalyst and application thereof.
[0013] In order to achieve the above invention object, the present invention adopts the following technical solutions:
[0014] A method for preparing a low chloride ion co-precipitation catalyst comprises the following steps:
[0015] (1) co-precipitating a metal salt solution and a precipitant solution;
[0016] (2) adjusting the pH of the product of step (1) using a precipitant solution, allowing the product to stand for aging, filtering, and washing;
[0017] (3) Add water to the product of step (2) to prepare a suspension, add an ion exchange resin loaded with modified hydrotalcite, heat it, adsorb it, filter the ion exchange resin to obtain a filtrate, filter the filtrate to obtain a filter cake, dry the filter cake, and calcine to obtain a catalyst.
[0018] In some specific embodiments, the metal salt in step (1) is a metal chloride having the chemical formula MCl x yH2O, metal chloride containing or not containing water of crystallization. Wherein M is selected from one or more of Ni, Co, Cu, Ru, Rh, Fe, Pd, Pt, Sn, Zn, Zr, Cr, Mo, Ce, La and Mg.
[0019] In some specific embodiments, the metal salt comprises one or more chlorides of Ni, Co, and Cu as the main catalyst source, and one or more chlorides of Ru, Rh, Fe, Pd, Pt, Sn, Zn, Zr, Cr, Mo, Ce, La, and Mg as the co-catalyst source.
[0020] In some specific embodiments, the precipitant solution is an alkali solution, preferably one or more of an aqueous solution of sodium carbonate, sodium bicarbonate, and ammonium carbonate, more preferably an aqueous solution of sodium carbonate.
[0021] In some specific embodiments, the temperature of step (1) is 55-85°C, preferably 60-70°C.
[0022] In some specific embodiments, in step (1), the pH of the solution is maintained between 7 and 8, preferably 7.2 and 7.6.
[0023] In some specific embodiments, stirring is performed in step (1) at a speed of 200-800 rpm.
[0024] In some specific embodiments, during the co-precipitation process in step (1), the dropping time is 2-10 hours, and after the dropwise addition of the metal salt solution is completed, the stirring is stopped.
[0025] In some specific embodiments, in step (2), a precipitant solution is used to adjust the pH of the product of step (1) to 7.2-7.5.
[0026] In some specific embodiments, in step (2), the static aging temperature is 50-80° C., and the aging time is 1-24 h, preferably 4-16 h.
[0027] In some specific embodiments, the deionized water used to wash the filter cake in step (2) is 3-5 times the volume of the filtrate, and the filter cake is washed 6-10 times.
[0028] In some specific embodiments, in step (3), the product of step (2) is added with water 4-10 times the volume of the product to prepare a solution, and an ion exchange resin loaded with modified hydrotalcite is added to the solution to adsorb the residual Cl - .
[0029] In some specific embodiments, the method for preparing the modified hydrotalcite-supported ion exchange resin comprises the following steps:
[0030] a. Liquid crystallization of a suspension containing water, hydrotalcite and carbon nanotubes to prepare modified hydrotalcite;
[0031] b. reacting water, modified hydrotalcite, polyol and ion exchange resin, filtering and drying.
[0032] In some specific embodiments, the general structural formula of the hydrotalcite in step a is Among them, M 2+ and N 3+ Respectively represent the divalent and trivalent metal cations in the laminate structure. The common M 2+ Metal cations include Mg 2+ , Ca 2+ , Fe 2+ One or more of the following, common N 3+ Trivalent metal cations include Al 3+ Cr 3+ , Fe 3+ One or more of the above. 2+ With N 3+ The molar ratio is 1-5:1.
[0033] As a preferred solution, in the step a, the mass ratio of hydrotalcite to carbon nanotube is (5-20):1, deionized water is added to prepare a 5-10wt% suspension, and stirred at 60-90°C for 4-24h. The stirred solution is transferred to a crystallization kettle lined with polytetrafluoroethylene, placed in an oven, and crystallized at a constant temperature of 120-180°C for 6-18h, and then cooled to room temperature to obtain the modified hydrotalcite.
[0034] As a preferred solution, the ion exchange resin is an acrylic acid-based weakly basic anion exchange resin, and the resin diameter is 1-3 mm.
[0035] As a preferred embodiment, in the step b, the mass ratio of modified hydrotalcite, polyol and ion exchange resin is (2-10): (0.5-3): 100, deionized water is added to prepare a 5-40wt% suspension, and the mixture is stirred at 50-90°C and 100-800 rpm for 1-10h, preferably at 60-80°C and 200-700 rpm for 4-8h.
[0036] As a preferred solution, in step b, the polyol is a difunctional or trifunctional small molecule polyol, including but not limited to one or more of ethylene glycol, propylene glycol, glycerol, trimethylolpropane, pentaerythritol, etc.
[0037] In some specific embodiments, the drying in step b is performed at 100-150° C. for 1-12 h.
[0038] In some specific embodiments, in step (3), the amount of the ion exchange resin supported by the modified hydrotalcite is 1-5 wt % of the product of step (2).
[0039] In some specific embodiments, in step (3), the temperature is raised to 150-180° C. and stirred for 1-10 hours for adsorption.
[0040] In some specific embodiments, in the step (3), after the adsorption is completed, the mixture is filtered using a 50-mesh sieve to obtain a filtrate; and the ion exchange resin is washed 4-8 times with deionized water to obtain a washing solution.
[0041] In some specific embodiments, in the step (3), the filtrate and the water washing liquid are mixed and filtered to obtain a filter cake, which is then dried at a temperature of 100-150° C. for 1-12 h; and the dried filter cake is calcined at 400-600° C. for 2-12 h.
[0042] On the other hand, the amination reaction catalyst prepared by the preparation method of the present invention has Cl - Content <20ppm.
[0043] In another aspect, the amination reaction catalyst prepared by the preparation method of the present invention is used in the amination reaction of polyether polyols and ammonia.
[0044] Preferably, the catalyst powder is pressed into tablets before use to obtain a cylindrical or spherical catalyst of 3-5 mm, and then the catalyst is loaded into a tubular reactor. The catalyst needs to be subjected to hydrogen reduction activation treatment before use. The activation temperature is 200-400°C, the hydrogen flow rate is 0.005-0.05g H2 / (g catalyst·h), and the activation time is 8-48h.
[0045] A method for preparing polyetheramine comprises the following steps: polyether polyol, ammonia and hydrogen react in the presence of an amination reaction catalyst.
[0046] In some specific embodiments, the polyether polyol is polymerized with propylene oxide using propylene glycol as an initiator, and the number average molecular weight is 230, 400, 600, 1000, 2000, or 5000.
[0047] In the preparation method of the polyetheramine, the space velocity of the polyether polyol is 0.3-2h -1 , the mass flow ratio of ammonia, hydrogen and polyether polyol is (0.8-2.5):(0.01-0.05):1.
[0048] In the preparation method of the polyetheramine, the reaction temperature is 160-220° C. and the reaction absolute pressure is 6-14 MPa.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] (1) Ion exchange resins have poor high temperature resistance and are easily deactivated at high temperatures. Since carbon nanotubes have the advantages of high strength, high electrical conductivity and high thermal conductivity, by loading carbon nanotube-modified hydrotalcite onto ion exchange resins, the heat generated by the reaction can be removed in a timely manner, which can greatly improve the high temperature resistance of ion exchange resins, thereby increasing the use temperature of the resins and greatly enhancing the ion adsorption capacity of the resins. The resins prepared by this method can be used at temperatures above 150°C.
[0051] (2) Due to its unique layered structure, hydrotalcite has interlayer anions that are exchangeable, giving it significant anion adsorption properties. Since the surface of hydrotalcite contains a large number of hydroxyl groups, the introduction of polyols forms hydrogen bonds between the polyols and hydrotalcite, which improves the binding force between the polyols and the hydrotalcite. At the same time, the remaining hydroxyl groups of the polyols can bind to the surface of the ion exchange resin, thereby greatly improving the loading capacity of the hydrotalcite on the ion exchange resin.
[0052] (3) Combined with acrylic acid weakly basic anion exchange resin itself to adsorb Cl - The modified hydrotalcite-loaded ion exchange resin can greatly reduce the Cl - The Cl content in the catalyst body is reduced. - The content of Cl - Poisoning the active components of the catalyst makes the catalyst more active. DETAILED DESCRIPTION
[0053] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0054] Gas chromatograph: Shimadzu GC-2014 (FID) detector, SE-30 capillary column, injection port 280 °C, detector 300 °C; heating program: 80 °C, constant temperature for 5 min, then increased to 280 °C at a rate of 30 °C / min, and maintained for 10 min.
[0055] The acrylic acid-based weakly alkaline anion exchange resins were purchased from Elest (Shanghai) New Material Technology Co., Ltd., with models of YLST-19, YLST-28 and YLST-29.
[0056] Example 1
[0057] Weigh 65.0g NiCl2, 65.0g CoCl2, 7.3g RhCl3 and 5.2g RuCl3 respectively, add to 2L deionized water to obtain a metal salt solution. Weigh 119.6g Na2CO3 and add to 2L deionized water to prepare a precipitant solution. Slowly add the precipitant solution to the salt solution, control the reaction temperature to 55°C, the stirring speed to 200 rpm, and keep the pH of the mixed solution at 7.0. After 2h of dropping, stop stirring and adjust the pH to 7.2. Let the precipitate stand at 50°C for 1h,
[0058] After aging, the obtained suspension was filtered, and the filter cake was washed with 3 times the volume of water and filtered, and the process was repeated 6 times to obtain a filter cake.
[0059] Mg 2+ / Al 3+ Hydrotalcite and carbon nanotubes with a molar ratio of 1 were added to deionized water in a mass ratio of 5:1 to prepare a 5wt% suspension, which was stirred at 60°C for 4 hours. The stirred solution was transferred to a crystallization kettle lined with polytetrafluoroethylene, placed in an oven, and crystallized at a constant temperature of 120°C for 6 hours. The solution was cooled to room temperature to obtain the modified hydrotalcite.
[0060] The modified hydrotalcite, ethylene glycol and YLST-19 acrylic weak alkaline anion exchange resin with a diameter of 1 mm were mixed in a mass ratio of 2:0.5:100, added to deionized water to prepare a 5wt% suspension, stirred at 50°C and 100 rpm for 1 hour, the solution was filtered to obtain the resin, and the resin was dried at 100°C for 1 hour to obtain the modified hydrotalcite-loaded ion exchange resin.
[0061] Add the modified hydrotalcite-loaded ion exchange resin to the suspension of catalyst and water in an amount of 1% of the catalyst filter cake mass, stir and heat, and stir at 150°C and 100 rpm for 1 hour to adsorb the Cl - Filter out the ion exchange resin using a 50-mesh sieve to obtain a filtrate. Wash the ion exchange resin with deionized water 4 times to obtain a water wash. Mix the filtrate and the water wash, filter to obtain a filter cake, dry the filter cake at 100°C for 1 hour, and calcine it at 400°C for 2 hours. Test the Cl content in the powder. -The content is 18ppm. The obtained catalyst powder is pressed into a 3mm cylindrical tablet, and the catalyst is loaded into a tubular reactor and activated with hydrogen. The activation temperature is 200°C, the hydrogen flow rate is 0.005gH2 / (g catalyst·h), and the activation time is 8h.
[0062] The catalyst was used for the amination reaction of 230 molecular weight polyether polyol with liquid ammonia, and the space velocity of the polyether polyol was 0.3h -1 , the mass flow ratio of liquid ammonia, hydrogen and polyether polyol is 0.8:0.01:1, the reaction temperature is 160℃, and the absolute pressure is 6MPa. After vacuum deamination and dehydration, the product is analyzed by gas chromatography, and the conversion rate of polyether polyol is 96.5% and the selectivity is 99.1%.
[0063] Comparative Example 1
[0064] The difference from Example 1 is that the hydrotalcite is not modified with carbon nanotubes, and other conditions remain unchanged. - The content is 420 ppm. Under the same reaction conditions as in Example 1, the product was analyzed by gas chromatography, and the conversion rate of the polyether polyol was 92.8% and the selectivity was 93.6%.
[0065] Comparative Example 2
[0066] The difference from Example 1 is that the hydrotalcite is not modified with polyols, and other conditions remain unchanged. - The content is 340 ppm. Under the same reaction conditions as in Example 1, the product was analyzed by gas chromatography, and the conversion rate of the polyether polyol was 93.1% and the selectivity was 94.3%.
[0067] Comparative Example 3
[0068] The difference from Example 1 is that the washed filter cake is treated with YLST-19 acrylic acid weak alkaline anion exchange resin, the ion exchange resin is not modified, and other conditions remain unchanged. - The content is 580 ppm. Under the same reaction conditions as in Example 1, the product was analyzed by gas chromatography, and the conversion rate of the polyether polyol was 90.2% and the selectivity was 92.4%.
[0069] Comparative Example 4
[0070] The difference from Example 1 is that the filter cake after washing is not treated with ion exchange resin, and the filter cake is directly pressed into tablets after drying, and other conditions remain unchanged. - The content is 1030 ppm. Under the same reaction conditions as in Example 1, the product was analyzed by gas chromatography, and the conversion rate of the polyether polyol was 86.5% and the selectivity was 89.4%.
[0071] Example 2
[0072] Weigh 65.0g CoCl2, 67g CuCl2, 1.6g FeCl3 and 1.8g PdCl2 respectively, add to 2L deionized water to obtain a metal salt solution. Weigh 110.8g Na2CO3 and add to 2L deionized water to prepare a precipitant solution. Slowly drop the precipitant solution into the salt solution, control the reaction temperature to 85°C, the stirring speed to 800 rpm, keep the pH of the mixed solution at 8, stop stirring after 10 hours of dropping, and adjust the pH to 7.5. Let the precipitate stand at 80°C for 24 hours,
[0073] After aging, the obtained suspension was filtered, and the filter cake was washed with 5 times the volume of water and filtered, and the process was repeated 10 times to obtain a filter cake.
[0074] Ca 2+ / Cr 3+ Hydrotalcite and carbon nanotubes with a molar ratio of 5 were added to deionized water in a mass ratio of 20:1 to prepare a 10wt% suspension, and stirred at 90°C for 24h. The stirred solution was transferred to a crystallization kettle lined with polytetrafluoroethylene, placed in an oven, and crystallized at a constant temperature of 180°C for 18h. The solution was cooled to room temperature to obtain the modified hydrotalcite.
[0075] The modified hydrotalcite, propylene glycol and YLST-28 acrylic acid weak alkaline anion exchange resin with a diameter of 3 mm were mixed in a mass ratio of 10:3:100, added into deionized water to prepare a 40wt% suspension, stirred at 90°C and 800 rpm for 10 hours, the solution was filtered to obtain a resin, and the resin was dried at 150°C for 12 hours to obtain an ion exchange resin loaded with modified hydrotalcite.
[0076] The modified hydrotalcite-loaded ion exchange resin was added to the catalyst aqueous solution in an amount of 5% of the catalyst filter cake mass, stirred and heated, and stirred at 180°C and 900 rpm for 10 h to adsorb the Cl - Filter out the ion exchange resin using a 50-mesh sieve to obtain a filtrate. Wash the ion exchange resin with deionized water 8 times to obtain a water wash. Mix the filtrate and the water wash, filter to obtain a filter cake, dry the filter cake at 150°C for 12 hours, and calcine it at 600°C for 12 hours. Test the Cl content in the powder. - The content is 10ppm. The obtained catalyst powder is pressed into 5mm spheres, the catalyst is loaded into a tubular reactor, and the catalyst is activated with hydrogen. The activation temperature is 400℃, the hydrogen flow rate is 0.05g H2 / (g catalyst·h), and the activation time is 48h.
[0077] The catalyst was used for the amination reaction of 400 molecular weight polyether polyol with liquid ammonia. The space velocity of the polyether polyol was 2h -1 The mass flow ratio of liquid ammonia, hydrogen and polyether polyol is 2.5:0.05:1, the reaction temperature is 220℃, and the absolute pressure is 14MPa. After vacuum deamination and dehydration, the product is analyzed by gas chromatography, and the conversion rate of polyether polyol is 98.4% and the selectivity is 99.6%.
[0078] Example 3
[0079] Weigh 65.0g NiCl2, 67g CuCl2, 13.3g PtCl3 and 13.1g SnCl4 respectively, add to 2L deionized water to obtain a metal salt solution. Weigh 137.0g Na2CO3 and add to 2L deionized water to prepare a precipitant solution. Slowly add the precipitant solution to the salt solution, control the reaction temperature to 70°C, the stirring speed to 500 rpm, and keep the pH of the mixed solution at 7.5. After 6 hours of dropping, stop stirring and adjust the pH to 7.3. Let the precipitate stand at 65°C for 12 hours.
[0080] After aging, the obtained suspension was filtered, and the filter cake was washed with 4 times the volume of water and filtered, and the process was repeated 8 times to obtain a filter cake.
[0081] Fe 2+ / Al 3+ Hydrotalcite and carbon nanotubes with a molar ratio of 3 were added to deionized water in a mass ratio of 15:1 to prepare an 8wt% suspension, and stirred at 75°C for 12 hours. The stirred solution was transferred to a crystallization kettle lined with polytetrafluoroethylene, placed in an oven, and crystallized at a constant temperature of 150°C for 12 hours. The solution was cooled to room temperature to obtain the modified hydrotalcite.
[0082] The modified hydrotalcite, glycerol and YLST-29 acrylic acid weak alkaline anion exchange resin with a diameter of 2 mm were mixed in a mass ratio of 6:1.5:100, added to deionized water to prepare a 20wt% suspension, stirred at 70°C and 450 rpm for 5 hours, the solution was filtered to obtain the resin, and the resin was dried at 125°C for 6 hours to obtain the modified hydrotalcite-loaded ion exchange resin.
[0083] The modified hydrotalcite-loaded ion exchange resin was added to the catalyst aqueous solution in an amount of 3% of the catalyst filter cake mass, stirred and heated, and stirred at 165°C at a speed of 500 rpm for 5 hours to adsorb the Cl -Filter out the ion exchange resin using a 50-mesh sieve to obtain a filtrate. Wash the ion exchange resin with deionized water for 6 times to obtain a water wash. Mix the filtrate and the water wash, filter to obtain a filter cake, dry the filter cake at 125°C for 6 hours, and calcine it at 500°C for 7 hours. Test the Cl content in the powder. - The content is 15ppm. The obtained catalyst powder is pressed into a 4mm cylindrical tablet, and the catalyst is loaded into a tubular reactor and activated with hydrogen. The activation temperature is 300°C, the hydrogen flow rate is 0.03g H2 / (g catalyst·h), and the activation time is 24h.
[0084] The catalyst was used for the amination reaction of 600 molecular weight polyether polyol with liquid ammonia. The space velocity of the polyether polyol was 1h -1 The mass flow ratio of liquid ammonia, hydrogen and polyether polyol is 1.5:0.03:1, the reaction temperature is 190°C, and the absolute pressure is 10MPa. After vacuum deamination and dehydration, the product is analyzed by gas chromatography, and the conversion rate of polyether polyol is 97.8% and the selectivity is 99.4%.
[0085] Example 4
[0086] Weigh 65.0g NiCl2, 32.5g CoCl2, 33.5g CuCl2, 2.0g ZnCl2 and 3.5g ZrCl4 respectively, add to 2L deionized water to obtain a metal salt solution. Weigh 115.2g Na2CO3 and add to 2L deionized water to prepare a precipitant solution. Slowly add the precipitant solution to the salt solution, control the reaction temperature to 60°C, the stirring speed to 400 rpm, and keep the pH of the mixed solution at 7.2. After 4 hours of dropping, stop stirring and adjust the pH to 7.4. Let the precipitate stand at 55°C for 4 hours.
[0087] After aging, the obtained suspension was filtered, and the filter cake was washed with 3 times the volume of water and filtered, and the process was repeated 7 times to obtain a filter cake.
[0088] Mg 2+ / Fe 3+ Hydrotalcite and carbon nanotubes with a molar ratio of 2 were added to deionized water in a mass ratio of 8:1 to prepare a 6wt% suspension, and stirred at 70°C for 8h. The stirred solution was transferred to a crystallization kettle lined with polytetrafluoroethylene, placed in an oven, and crystallized at a constant temperature of 140°C for 10h. The solution was cooled to room temperature to obtain the modified hydrotalcite.
[0089] The modified hydrotalcite, trimethylolpropane and YLST-19 acrylic weak alkaline anion exchange resin with a diameter of 1 mm were mixed in a mass ratio of 4:1:100, added to deionized water to prepare a 10wt% suspension, stirred at 60°C and 200 rpm for 4 hours, the solution was filtered to obtain a resin, and the resin was dried at 110°C for 4 hours to obtain an ion exchange resin loaded with modified hydrotalcite.
[0090] The modified hydrotalcite-loaded ion exchange resin was added to the catalyst aqueous solution in an amount of 2% of the catalyst filter cake mass, stirred and heated, and stirred at 160°C and 300 rpm for 3 h to adsorb the Cl - Filter out the ion exchange resin using a 50-mesh sieve to obtain a filtrate. Wash the ion exchange resin with deionized water for 5 times to obtain a water wash. Mix the filtrate and the water wash, filter to obtain a filter cake, dry the filter cake at 110°C for 3h, and calcine it at 450°C for 4h. Test the Cl content in the powder. - The content is 16ppm. The obtained catalyst powder is pressed into 3mm spheres, the catalyst is loaded into a tubular reactor, and the catalyst is activated with hydrogen. The activation temperature is 250°C, the hydrogen flow rate is 0.01g H2 / (g catalyst·h), and the activation time is 12h.
[0091] The catalyst was used for the amination reaction of 1000 molecular weight polyether polyol with liquid ammonia, and the space velocity of the polyether polyol was 0.8h -1 The mass flow ratio of liquid ammonia, hydrogen and polyether polyol is 1:0.02:1, the reaction temperature is 170°C, and the absolute pressure is 8MPa. After vacuum deamination and dehydration, the product is analyzed by gas chromatography, and the conversion rate of polyether polyol is 97.1% and the selectivity is 99.2%.
[0092] Example 5
[0093] Weigh 32.5g NiCl2, 65.0g CoCl2, 33.5g CuCl2, 6.3g CrCl3 and 10.9g MoCl5 respectively, add to 2L deionized water to obtain a metal salt solution. Weigh 132.8g Na2CO3 and add to 2L deionized water to prepare a precipitant solution. Slowly add the precipitant solution to the salt solution, control the reaction temperature to 70°C, the stirring speed to 600 rpm, and keep the pH of the mixed solution at 7.6. After 8 hours of dripping, stop stirring and adjust the pH to 7.2. Let the precipitate stand and age at 75°C for 16 hours.
[0094] After aging, the obtained suspension was filtered, and the filter cake was washed with 5 times the volume of water and filtered, and the process was repeated 9 times to obtain a filter cake.
[0095] Ca2+ / Al 3+ Hydrotalcite and carbon nanotubes with a molar ratio of 4 were added to deionized water in a mass ratio of 18:1 to prepare a 9wt% suspension, and stirred at 80°C for 20h. The stirred solution was transferred to a crystallization kettle lined with polytetrafluoroethylene, placed in an oven, and crystallized at a constant temperature of 160°C for 16h. The solution was cooled to room temperature to obtain the modified hydrotalcite.
[0096] The modified hydrotalcite, pentaerythritol and YLST-28 acrylic weak alkaline anion exchange resin with a diameter of 3 mm were mixed in a mass ratio of 8:2:100, added into deionized water to prepare a 30wt% suspension, stirred at 80°C and 700 rpm for 8 hours, the solution was filtered to obtain a resin, and the resin was dried at 140°C for 8 hours to obtain an ion exchange resin loaded with modified hydrotalcite.
[0097] The modified hydrotalcite-loaded ion exchange resin was added to the catalyst aqueous solution in an amount of 4% of the catalyst filter cake mass, stirred and heated, and stirred at 170°C and 800 rpm for 8 hours to adsorb the Cl - Filter out the ion exchange resin using a 50-mesh sieve to obtain a filtrate. Wash the ion exchange resin with deionized water 7 times to obtain a water wash. Mix the filtrate and the water wash, filter to obtain a filter cake, dry the filter cake at 140°C for 10 hours, and calcine it at 550°C for 10 hours. Test the Cl content in the powder. - The content is 12ppm. The obtained catalyst powder is pressed into a 5mm cylindrical tablet, and the catalyst is loaded into a tubular reactor and activated with hydrogen. The activation temperature is 350°C, the hydrogen flow rate is 0.04g H2 / (g catalyst·h), and the activation time is 36h.
[0098] The catalyst was used for the amination reaction of 2000 molecular weight polyether polyol with liquid ammonia. The space velocity of the polyether polyol was 1.4h -1 , the mass flow ratio of liquid ammonia, hydrogen and polyether polyol is 2:0.04:1, the reaction temperature is 210℃, and the absolute pressure is 12MPa. After vacuum deamination and dehydration, the product is analyzed by gas chromatography, and the conversion rate of polyether polyol is 98.0% and the selectivity is 99.5%.
[0099] Example 6
[0100] Weigh 32.5g NiCl2, 32.5g CoCl2, 67g CuCl2, 7.4g CeCl3 and 7.4g LaCl3 respectively, add to 2L deionized water to obtain a metal salt solution. Weigh 122.5g Na2CO3 and add to 2L deionized water to prepare a precipitant solution. Slowly add the precipitant solution to the salt solution, control the reaction temperature to 80°C, the stirring speed to 550 rpm, and keep the pH of the mixed solution at 7.8. After 5 hours of dropping, stop stirring and adjust the pH to 7.5. Let the precipitate stand at 70°C for 10 hours.
[0101] After aging, the obtained suspension was filtered, and the filter cake was washed with 4 times the volume of water and filtered, and the process was repeated 8 times to obtain a filter cake.
[0102] Mg 2+ / Cr 3+ Hydrotalcite and carbon nanotubes with a molar ratio of 3 were added to deionized water in a mass ratio of 10:1 to prepare a 7wt% suspension, and stirred at 85°C for 10 hours. The stirred solution was transferred to a crystallization kettle lined with polytetrafluoroethylene, placed in an oven, and crystallized at a constant temperature of 170°C for 8 hours. The solution was cooled to room temperature to obtain the modified hydrotalcite.
[0103] The modified hydrotalcite, ethylene glycol and YLST-29 acrylic weak alkaline anion exchange resin with a diameter of 2 mm were mixed in a mass ratio of 5:1.5:100, added into deionized water to prepare a 25 wt% suspension, stirred at 55°C and 500 rpm for 6 h, the solution was filtered to obtain the resin, and the resin was dried at 120°C for 7 h to obtain the modified hydrotalcite-loaded ion exchange resin.
[0104] The modified hydrotalcite-loaded ion exchange resin was added to the catalyst aqueous solution in an amount of 5% of the catalyst filter cake mass, stirred and heated, and stirred at 155°C and 400 rpm for 6 hours to adsorb the Cl - Filter out the ion exchange resin using a 50-mesh sieve to obtain a filtrate. Wash the ion exchange resin with deionized water for 5 times to obtain a water wash. Mix the filtrate and the water wash, filter to obtain a filter cake, dry the filter cake at 130°C for 8 hours, and calcine it at 500°C for 6 hours. Test the Cl content in the powder. - The content is 17ppm. The obtained catalyst powder is pressed into 4mm spheres, and the catalyst is loaded into a tubular reactor and activated with hydrogen. The activation temperature is 280°C, the hydrogen flow rate is 0.025g H2 / (g catalyst·h), and the activation time is 30h.
[0105] The catalyst was used for the amination reaction of 5000 molecular weight polyether polyol with liquid ammonia, and the space velocity of the polyether polyol was 1.2h-1 The mass flow ratio of liquid ammonia, hydrogen and polyether polyol is 1.2:0.03:1, the reaction temperature is 180℃, and the absolute pressure is 9MPa. After vacuum deamination and dehydration, the product is analyzed by gas chromatography, and the conversion rate of polyether polyol is 97.6% and the selectivity is 99.3%.
Claims
1. A method for preparing a low chloride ion co-precipitation catalyst, comprising the following steps: (1) co-precipitating a metal salt solution and a precipitant solution; (2) adjusting the pH of the product of step (1) using a precipitant solution, allowing the product to stand for aging, filtering, and washing; (3) Add water to the product of step (2) to prepare a suspension, add an ion exchange resin loaded with modified hydrotalcite, heat it, adsorb it, filter the ion exchange resin to obtain a filtrate, filter the filtrate to obtain a filter cake, dry the filter cake, and calcine to obtain a catalyst.
2. The method according to claim 1, characterized in that The metal salt in step (1) is a metal chloride, the chemical formula of which is MCl x ·yH2O, metal chloride contains or does not contain water of crystallization, wherein M is selected from one or more of Ni, Co, Cu, Ru, Rh, Fe, Pd, Pt, Sn, Zn, Zr, Cr, Mo, Ce, La and Mg.
3. The method according to claim 1 or 2, characterized in that: The metal salt comprises one or more chlorides of Ni, Co, and Cu as a main catalyst source, and one or more chlorides of Ru, Rh, Fe, Pd, Pt, Sn, Zn, Zr, Cr, Mo, Ce, La, and Mg as a co-catalyst source.
4. The method according to any one of claims 1 to 3, characterized in that: The method for preparing the modified hydrotalcite-loaded ion exchange resin comprises the following steps: a. Liquid crystallization of a suspension containing water, hydrotalcite and carbon nanotubes to prepare modified hydrotalcite; b. reacting water, modified hydrotalcite, polyol and ion exchange resin, filtering and drying.
5. The method according to claim 4, characterized in that The general structural formula of hydrotalcite in step a is Among them, M 2+ and N 3+ represent divalent and trivalent metal cations in the lamellar structure, respectively, and the M 2+ Metal cations include Mg 2+ , Ca 2+ , Fe 2+ One or more of the N 3+ Metal cations include Al 3+ Cr 3+ , Fe 3+ One or more of; wherein M 2+ With N 3+ The molar ratio is 1-5:
1.
6. The method according to claim 4 or 5, characterized in that: In the step a, the mass ratio of hydrotalcite to carbon nanotubes is 5-20:1, deionized water is added to prepare a 5-10wt% suspension, stirred at 60-90°C for 4-24h, crystallized at a constant temperature of 120-180°C for 6-18h, and cooled to room temperature to obtain the modified hydrotalcite.
7. The method according to any one of claims 4 to 6, characterized in that: In the step b, the polyol is a difunctional or trifunctional small molecule polyol, preferably one or more of ethylene glycol, propylene glycol, glycerol, trimethylolpropane, and pentaerythritol.
8. The method according to any one of claims 4 to 7, characterized in that: In the step (3), the calcination is carried out at 400-600° C. for 2-12 hours.
9. The method according to any one of claims 4 to 8, characterized in that: The Cl in the catalyst - Content <20ppm.
10. A method for preparing a polyetheramine, comprising the following steps: The polyether polyol, ammonia and hydrogen react in the presence of the catalyst described in any one of claims 1 to 9.
Citation Information
Patent Citations
A catalyst for the reductive amination of octanol to synthesize octylamine and its preparation method.
CN103657682B
Method for the production of ethyleneamines
CN110709379A
Method for the production of ethyleneamines
CN110785400A
Method for the production of ethyleneamines
CN113474326A